2014
DOI: 10.1525/jer.2014.9.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Building from the inside Out: Development and Evaluation of a CITI Ethics Certification Training Module for American Indian and Alaska Native Community Researchers

Abstract: Current Human Subject Research training modules fail to capture ethically relevant cultural aspects of research involving American Indian and Alaska Native (AI/AN) community members. Applying a Community Engaged Research (CEnR) approach, we adapted the Collaborative IRB Training Initiative training module “assessing risk and benefits.” In a two-arm randomized controlled trial, followed by debriefing interviews, we evaluated module acceptability and understandability (test scores) among 40 reservation-based com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Previous research has shown that the use of CEnR with the intended population improves the quality of researcher training materials, resulting in higher scores on relevance of the material, overall satisfaction, module quiz scores, and a trend toward higher self-efficacy [11]. By conducting focus groups with IFRs and other vulnerable populations, the final curriculum included material directly contributed by the population under study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that the use of CEnR with the intended population improves the quality of researcher training materials, resulting in higher scores on relevance of the material, overall satisfaction, module quiz scores, and a trend toward higher self-efficacy [11]. By conducting focus groups with IFRs and other vulnerable populations, the final curriculum included material directly contributed by the population under study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Community Engaged Research (CEnR) plays a significant role for outreaching to IFR and racial/ethnic minority populations [10] by providing the researcher with an understanding of what a new innovation means to a specific community. The insights and perspectives gained from outreach to IFR and racial/ethnic minority populations can inform the development and evaluation of human subjects’ protections training materials [11]. …”
Section: Introductionmentioning
confidence: 99%
“…These standard research ethics training modules have been translated into other languages (i.e., Spanish, Japanese, and Korean). However, in community-engaged research, research ethics training issues remain related to cultural and contextual relevance, risks and benefits of research to communities, and areas of confusion to community members engaged in research (4,5). Pearson and colleagues’ (5) work with American Indians and Alaska Natives demonstrated that adaptations to human subjects protection training should include issues that are pertinent to ethnic minority communities, references to specific cultures, use of simplified terminology and clarification of concepts, examples relevant to communities (e.g., misuse of data), and topics related to community-level risk and benefits (e.g., discomfort or distress from discussing traumatic events).…”
Section: Introductionmentioning
confidence: 99%
“…As the role of community members in research grows, so does concern over the ethical research training they receive (5,15,16). Research in communities may lead to different research ethical challenges than those in traditional academic and clinical settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation